1994
DOI: 10.1111/j.1467-8624.1994.tb00790.x
|View full text |Cite
|
Sign up to set email alerts
|

A Factor Analytic Study of the Infant-Toddler and Early Childhood Versions of the HOME Inventory Administered to White, Black, and Hispanic American Parents of Children Born Preterm

Abstract: Factor analyses were performed on the Infant-Toddler and the Early Childhood versions of the HOME Inventory for 3 groups (blacks, whites, and Hispanics) of premature, low-birthweight children. Participants lived in 8 different U.S. cities. On the IT-HOME, 5 factors were originally retained for each group using the principal factors method of extraction. Factor structures for blacks and whites were similar, accounting for 85% and 75% of the variance, respectively. The structure for Hispanics was somewhat differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 20 publications
2
36
0
3
Order By: Relevance
“…This finding of general equivalence across racial groups is consistent with other studies of parenting (Bradley et al, 1994;Sugland et al, 1995;Whiteside-Mansell et al, 2001) that also found more similarity than not in the way in which parenting behaviors were organized (factor structure) in African American and European American families. Evidence for equivalence has emerged when narrowly defined aspects of parenting obtained from video coded data were studied (Whiteside-Mansell et al, 2001) and when more broadly defined dimensions of parenting coded in a combination of semistructured interviews and real-time coded observational coding were used (Bradley et al, 1994;Sugland et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding of general equivalence across racial groups is consistent with other studies of parenting (Bradley et al, 1994;Sugland et al, 1995;Whiteside-Mansell et al, 2001) that also found more similarity than not in the way in which parenting behaviors were organized (factor structure) in African American and European American families. Evidence for equivalence has emerged when narrowly defined aspects of parenting obtained from video coded data were studied (Whiteside-Mansell et al, 2001) and when more broadly defined dimensions of parenting coded in a combination of semistructured interviews and real-time coded observational coding were used (Bradley et al, 1994;Sugland et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have measured the full extensiveness of the construct, and most scholars would not argue that a parent has to be high on every dimension to be considered sensitive. Bradley, Mundfrom, Whiteside, Casey, and Barrett (1994) examined the factor structure of a semistructured interview observational assessment of parenting using exploratory factor analyses and found a similar structure for parental responsiveness across Black and White families. The comparability of maternal responsiveness across cultural groups has drawn attention because some aspects of it have been shown to be similar across some groups, whereas other aspects have been shown to be unique depending on the culture (Bornstein et al, 1992).…”
Section: Dimensions Of Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Covariates considered were child age at each study time point, child sex, family SES, 21 family stress, 22 mothers’ IQ, 23 mothers’ depressive symptoms, 24 mothers’ highest level of education, and the emotional and material support provided in the child’s home environment. 25 Maternal depressive symptoms, years of education, and IQ were not related to any of the study variables and were not considered further. All other covariates considered were included as controls.…”
Section: Methodsmentioning
confidence: 99%
“…In order to answer the question of whether or not postnatal growth was related to SES and how family environment might mediate these relationships, we used data on birth weight and length and 12-month weight, length, SES and variables from the Home Observation for Measurement of the Environment (HOME) [31] from a large, longitudinal cohort of Chilean infants. This allowed us to establish direct and indirect associations between SES, family factors and infant growth.…”
Section: Introductionmentioning
confidence: 99%